Pengaruh Implementasi Ekonomi Islam Dalam Membentuk Karakter Masyarakat Yang Islami - Wardani, Ach. Khiarul Waro (Universitas Islam Tribakti Lirboyo Kediri, 2020)
Islamic economy is in the middle of a developed society model which becomes a separate measure or barometer for practicing all transactions based on uluhiyah and insaniyha. As a representative of Islamic teachings that are able to provide benefits to all living things, Islamic economy is able to provide movement and influence on society in its economic practices. Islamic economics as part of the social sector tries to offer an economic action that is beneficial to all economic and social actors, which makes the existence of Islamic economics as a means of self-revolution from a capitalist concept that prioritizes personal gain towards Islamic behavior, namely prioritizing interests vertically (after all: God ) and horizontal interests (humanity). The implementation of Islamic economics emerges from a set of basic Islamic laws, namely: Al-Quran and Hadith as the primary law and the ulama's ijtihad as the primary legal basis. Prophet Muhammad SAW, his companions and tabi'i, tabi'in and scholars in the past and present are a reflection of the level of building a good relationship with the progress of Islam as a civilized religion and as a barometer for shaping an Islamic character, namely upholding the values human value. In conditions like this, when mankind begins to neglect their own brothers because of their own enrichment (capitalism) so that they become uncivilized human beings, then here God's lovers give an example which then influences humans to become Islamic humans through the means of preaching, namely the concept. application or implementation of Islamic economics.